Loneliness and nervousness mediated the longitudinal association between sleep disorders and cyberbullying victimization in school-aged adolescents - Xiao, Xin; Jiang, Zu-Ling; Lei, Qiong; Wang, Si-Jia; Li, Si-Xuan; Gong, Qing-Hai (Frontiers in Psychiatry, 2025)
BackgroundThis study investigated the longitudinal dose–response relationship between sleep disorders and cyberbullying victimization in school-aged adolescents and explored the mediating roles of psychological factors (loneliness, sadness, and nervousness).MethodsA 2-year longitudinal design was used to collect self-reported data on sleep disorders, physical activity, screen time, smoking, alcohol use, and dieting behavior. Cyberbullying victimization was assessed during follow-up. Multivariate logistic regression analysis and restricted cubic splines (RCSs) were used to analyze the dose–response relationship between sleep disorders and cyberbullying victimization. The mediation analysis explored indirect effects through loneliness, sadness, and nervousness.ResultsAmong the 1,910 adolescents (mean age: 12.2 ± 0.47 years), the mean sleep disorder score was 3.32 ± 3.68 (range: 0–27.0), and 196 (10.3%) engaged in cyberbullying victimization during the follow-up period. Sleep disorders were significantly associated with an increased risk of cyberbullying victimization (OR: 1.10, 95% CI: 1.06–1.14) after adjusting for confounders. Sensitivity analyses further validated the robustness of the results, which revealed that the risk of cyberbullying victimization increased approximately with increasing prevalence of sleep disorders. The RCS curve revealed that the risk of cyberbullying victimization increased approximately linearly with increasing prevalence of sleep disorders (P for overall<0.001, P for nonlinear=0.915). Compared with boys, girls with more sleep disorders presented a slightly greater risk of cyberbullying victimization (adjusted OR: 1.14 vs.1.08). Loneliness and nervousness partially mediated the association between sleep disorders and cyberbullying victimization, accounting for 25.00% (indirect effect β = 0.003, P < 0.001) and 8.33% (indirect effect β = 0.001, P = 0.038) of the total effect, whereas sadness had no significant effect.ConclusionsSleep disorders independently predict cyberbullying victimization in adolescents, with stronger effects observed in girls. Loneliness and nervousness partially mediate this association. Targeted interventions to improve sleep, reduce loneliness and nervousness, and sex-specific strategies may mitigate cyberbullying victimization in school-aged adolescents.